Effects of condensed tannins of some tropical plants on ruminal gas production in vitro - Petlum, Anan; Paengkoum, Pramote; Liang, Juan Boo; Vasupen, Kraisit; Wilachai, K.; Onjai-uea, N. (2015)
The objectives of this study was to investigate the effect of condensed tannins (CTs) in some tropical plants species on in vitro ruminal gas production. Three plant species, include leucaena (Leucaena leucocephala) (LN), cassava (Manihot esculenta, Cranzt) (CV), and Siam neem (Azadirachta indica A. Juss. var. siamensis Valeton) (SN) (CTs contained at 2.9, 1.2 and 5.0 % of DM, respectively) were selected to use in this study.Plant species had effect on in vitro gas kinetic parameters and gas productions (P<0.01). However, only high concentration of CTs in SN (5.0% of DM) showed the inhibitory effect on the insoluble fractions and methane production at 48 h of incubation. The results suggested that various plant species contained different concentration of CTs had different effect on in vitro gas and methane production, however, others factors affected on biological properties of CTs, such as molecular weight and structure should be further investigated.